An Annotated Translation of Bicycle Shop Murder - Firstiyanti, Aulia Haris (LADU: Journal of Languages and Education, 2021)
Background: This research article is focusing on annotated translation to describe and give plausible reasons in solving the translation problems.Purpose: The purposes of this study are: (1) to attain information concerning the difficulties faced by the researcher while translating the source text, and (2) to give plausible translation reasons to the difficulties.Design and methods: Introspective and retrospective methods are employed to explore the plausible translation on Bicycle Shop Murder novel. Data findings are validated using translation strategies by Chesterman.Results: As the researcher tries to figure out problems during the process of translation by giving annotation for each data, it shows that from the 30 data chosen to be analyzed, there are: two (2) literal translation, two (2) loan, two (2) calque, two (2) transposition, two (2) clause structure change, two (2) phrase structure change, two (2) synonymy, two (2) antonymy, four (4) distribution change consisting of two (2) compression and two (2) expansion, two (2) paraphrase, two (2) naturalization, two (2) coherence change, two (2) explicitness change from implicit into explicit, and two (2) interpersonal change used to solve these problems.